Tendências das Infecções em uma Unidade de Terapia Intensiva Neonatal ao longo de sete anos e meio - Ferreira, Isadora Caixeta da Silveira (2024)
Introduction: Healthcare-Associated Infections (HAIs) pose a risk to critically ill neonates, especially in the presence of antimicrobial resistance, necessitating an understanding of epidemiological aspects, including intestinal colonization, to reduce morbidity and mortality. Objective: To conduct an epidemiological study of Gram-negative bacteria (GNB) intestinal colonization, invasive infection by oxacillin-resistant Staphylococcus spp. (ORS), neonatal conjunctivitis, and urinary tract infection (UTI) in the Neonatal Intensive Care Unit (NICU) of the Hospital de Clínicas da Universidade Federal de Uberlândia (HC-UFU). Material and Methods: This is a descriptive retrospective observational cohort study conducted through the medical records of neonates admitted to the NICU between January 2015 and June 2022. Patients were monitored daily using epidemiological forms from the National Healthcare Safety Network. This study was approved by the UFU Research Ethics Committee (number 2,173,884/2017). Results: Of the neonates admitted to the NICU, 6.9% had GNB intestinal colonization, 12% had invasive ORS infection, 12.3% had bacterial conjunctivitis, and 3.9% had UTI. The incidence per 1,000 patient-days showed a reduction in GNB intestinal colonization (6.4 to 1.5) between 2018 and 2022, in invasive ORS infections (8.3 to 4), and in conjunctivitis (14.1 to 9) from 2016 to 2022, and an increase in UTI (0.1 to 2.1) between 2015 and 2022. Among intestinal GNB, 16.7% produced extended-spectrum beta-lactamase (ESBL), and 27.4% were carbapenem-resistant. Conjunctivitis was primarily caused by Gram-positive bacteria (GPB) (62.1%), and of the total isolates, 48.6% were multidrug-resistant (MDR). In contrast, 18.3% of uropathogens were MDR, with the majority being GNB (74.6%). Previous antimicrobial prescription and invasive device use increased the risk of GNB intestinal colonization and HAIs. GNB intestinal colonization and infections prolonged hospital stay, and GNB intestinal colonization and invasive ORS infection were associated with higher mortality. Conclusion: Early detection of GNB intestinal colonization is crucial for preventing invasive infections. Despite the decrease in ORS and conjunctivitis incidence, there was an increase in UTI, especially due to MDR uropathogens, intensified by previous antimicrobial prescription and invasive device use. Infections, especially MDR ones, contributed to prolonged hospitalization and lethality. These findings underscore the urgency of infection prevention and control measures to mitigate severe neonatal complications.